The curse of the lost cave - Bearce, Stephanie (Bearce, Stephanie. Raven Gallows mystery., 2026)
"Raven Gallows and her friends hunt for the treasure of legendary outlaw Alf Bolin, facing rival treasure hunters, cryptic riddles, and conspiracies tied to a shadowy corporation"-- Provided by publisher.